Pengklitikan enklitik "-nya" pada kata kerja: aplikasi Teori Kuasaan dan Tambatan (Chomsky, 1986) (Jurnal Bahasa, 2006)
This study claims that cliticization is not a morphological process but a syntactical process. It argues that enclitic -"nya" is a lexical item in the lexicon of a Malay native speaker. Cliticization is a process of adjunction of a lexical item to its host. This study claims that cliticization happens at the syntactic level. C'liticization at this level is influenced by two types of syntactic analysis which are movement hyphotesis and in situ hyphotesis. Movement hyphotesis claims that a clitic existed on the complement position of its host at the D-structure and moves to adjoin to its host at the L-structure through the move-alpha transformation. On the other hand, in situ hyphotesis claims that a clitic is adjoined to its host at the D-structure, therefore, at the L-structure it doesn't have to move. There are few mechanism that need to be brought forward in order to defend the in situ hyphotesis analysis. Therefore, movement hyphotesis will be argued as the best hyphotesis to be adapted in order to explain the cliticization of enclitic "-nya" to the verbs at the L-structure.